Facilitators' experience of delivering asynchronous and synchronous online interprofessional education. (December 2014) - Evans, Sherryn; Knight, Tess; Sønderlund, Anders; Tooley, Gregory
Abstract: Introduction : Online delivery of interprofessional education (IPE) is an emerging area with very little research to date focusing on the experience of the facilitator in this process. The purpose of this article was to explore the facilitator experience of online asynchronous and synchronous IPE facilitation of pre-licensure students. Methods : Nineteen online facilitators participated in semi-structured telephone interviews to explore this experience. Results : Findings from Interpretative Phenomenological Analysis indicated that the facilitators found positives of the experience including perceiving that the students were learning, their own development as a facilitator, the flexibility of the role and feeling supported as a facilitator. Challenges of the experience were also noted including technological problems in the synchronous environment and engaging some students or teams in both the synchronous and asynchronous environments. Discussion : While this study identified positive aspects of the facilitation experience it also highlighted some key topics which need to be addressed in training for online IPE facilitators to further enhance their experience, and subsequently the experience and interprofessional learning of their students.